Institutional and policy adjustments to implement Free Trade Agreements with the European Union: A developing country perspective - Kenneth Baltzer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Free Trade Agreements (FTAs) between the European Union (EU) and trade partners go far beyond mere elimination of tariffs to include such diverse issues as non-tariff barriers, competition legislation, investment protection, and more. Implementing such provisions requires deep institutional and policy adjustments. This report reviews the international experiences with institutional and policy adjustments needed to implement FTAs with the EU, as seen from a developing country perspective. It focuses on three issues: investment, competitiveness, and competition, including state-owned enterprise reform. The report concludes that the FTAs represent significant challenges for developing countries, but also potential opportunities for a more efficient trading system.
Keywords: F13; K33; O17; 330; developing countries; European Union; Free Trade Agreement; institutional development; policy adjustment